2012
DOI: 10.1002/mana.201100045
|View full text |Cite
|
Sign up to set email alerts
|

Positivity properties for the clamped plate boundary problem on the ellipse and strip

Abstract: The positivity preserving property for the biharmonic operator with Dirichlet boundary condition is investigated. We discuss here the case where the domain is an ellipse (that may degenerate to a strip) and the data is a polynomial function. We provide various conditions for which the positivity is preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…To argue the optimality and the consistency of our approach, we remark that the root of the mapping a → h(a, 2) can be computed numerically, and it is given by b 0 ≈ 18.94281916344395 (see Figure 3), which is the same threshold found in [28,Theorem 5.2], obtained with different arguments than ours in the study of the bilaplacian in two-dimensional ellipses. Proof of Corollary 1.7.…”
Section: Extended Range For Counterexamplessupporting
confidence: 69%
See 1 more Smart Citation
“…To argue the optimality and the consistency of our approach, we remark that the root of the mapping a → h(a, 2) can be computed numerically, and it is given by b 0 ≈ 18.94281916344395 (see Figure 3), which is the same threshold found in [28,Theorem 5.2], obtained with different arguments than ours in the study of the bilaplacian in two-dimensional ellipses. Proof of Corollary 1.7.…”
Section: Extended Range For Counterexamplessupporting
confidence: 69%
“…iv) A thorough analysis for s = n = 2 is performed in [28], finding a counterexample in terms of a polynomial of degree 6 in an ellipse with axes ratio equal to √ 19 ≈ 4.359. The authors also show that it is not possible to construct a counterexample in an ellipse with polynomials of degree less than 6; moreover, it is also shown that counterexamples with degree 6 polynomials are only possible if the axes ratio is larger than ≈ 4.352 (this threshold also appears in our analysis, see Section 4.1).…”
Section: Introductionmentioning
confidence: 99%